2021
DOI: 10.3390/en14113103
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Creep Acoustic Emission Characteristics of Coal Bodies around Boreholes under Different Moisture Contents

Abstract: Water content is an important factor in the deformation-destruction process of coal bodies. To analyze the influence of water on the creep acoustic emission (AE) characteristics of coal rock surrounding a borehole, we conducted graded loading creep AE tests of single-hole specimens with different water contents (0%, 4%, 8% and water-saturation) under uniaxial loading. The findings include the following: the water content affects the creep mechanical properties of the coal body around a borehole. The creep tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Numerous research results have shown that AE ringing count is a characteristic parameter that can well reflect the variety of material properties because it is proportional to the strain energy released by the motion of dislocations and crack extension inside the material [9,47,48]. Therefore, AE ringing counts and cumulative ringing counts are used as parameters to represent the damage evolution of non-corroded and corroded beams.…”
Section: Failure Stage Analysis Of Beamsmentioning
confidence: 99%
“…Numerous research results have shown that AE ringing count is a characteristic parameter that can well reflect the variety of material properties because it is proportional to the strain energy released by the motion of dislocations and crack extension inside the material [9,47,48]. Therefore, AE ringing counts and cumulative ringing counts are used as parameters to represent the damage evolution of non-corroded and corroded beams.…”
Section: Failure Stage Analysis Of Beamsmentioning
confidence: 99%
“…In the process of gas management, the hole formation quality of a gas extraction borehole is an important factor in determining the efficiency of gas extraction [5][6][7][8][9]. Under the influence of ground stress and mining, gas extraction boreholes are prone to collapse and deformation, which seriously affects gas management [10,11]. Borehole monitoring is a prerequisite to solving the problem of borehole collapse, can obtain the status information of the borehole, and can effectively prevent the occurrence of borehole collapse, as well as provide services to optimize the arrangement of the borehole, playing a positive role in deepening the process of drilling refinement operation, and greatly improving the effect of gas extraction in a borehole [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%